Potential impact of organic ligands on the antibacterial activity of silver nanoparticles. (29th January 2019) - Xue, Peng; Shan, Yixuan; Shen, Qihui; Li, Yingdi; Jiang, Jiayu; Liu, Yan; Liu, Xiaoyang
Abstract : Organic functional group ligands were connected to silica submicrospheres, and the antibacterial activity of AgNPs with ligands was compared with that of bare AgNPs. Abstract : The synthesis of Ag nanoparticles (AgNPs) frequently requires the participation of organic ligands. However, how the organic ligands attached on their surfaces would affect the antibacterial activity of the AgNPs remains to be explored. Based on a novel in situ synthesis approach, silica supported AgNPs with bare surfaces were fabricated and further functionalized with different organic ligands (–OH, –Ph, –SH, and –COOH) and the antibacterial activities of the bare AgNPs and AgNPs with different ligands were investigated. Though all specimens exhibited different antibacterial capabilities against Escherichia coli ( E. coli ), the minimal inhibitory concentration (MIC) of AgNPs functionalized with –COOH was the smallest and as low as 8–16 μg ml −1, indicating the best antibacterial performance among the 4 ligands. In addition, the cytotoxicity test of the bare AgNPs and AgNPs with ligands indicated that all the AgNPs caused no significant damage to human cells, suggesting their good potential for antibacterial applications in daily life.